AgNb0. 5Zr0. 25Mg0. 25O3 / ZrSiO4 composite ceramic with high energy storage density and preparation method thereof
Through B-position ion doping and second phase composite technology, AgNb0.5Zr0.25Mg0.25O3/ZrSiO4 composite ceramics were prepared, which solved the problems of breakdown field strength and low energy storage density of ceramic dielectrics, and achieved high breakdown resistance and high energy storage density ceramic materials, suitable for pulse power energy storage capacitors.
Patent Information
- Application Number
- CN202411817919.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-14
AI Technical Summary
Existing ceramic dielectrics are easily broken down at lower electric fields, resulting in low breakdown resistance field strength and insufficient energy storage density, which limits their application in the energy storage field.
AgNb0.5Zr0.25Mg0.25O3/ZrSiO4 composite ceramics were prepared by B-position ion doping combined with the second phase recombination method, nanopowders were prepared by hydrothermal method, ball milling and tablet forming, and finally high-pressure sintering was used to obtain Dense composite ceramics.
The breakdown field strength and energy storage density of composite ceramics are significantly improved, with a breakdown field strength of 750kV/cm and a maximum energy storage density of 7.73J/cm3. It also has good temperature stability and low cost characteristics.
Smart Images

Figure CN119430929A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a high energy storage density composite ceramic. Background Art
[0002] High energy storage density capacitors have the advantages of large discharge power, high utilization efficiency, fast charge and discharge speed, and stable performance. They play an important role in power systems, electronic devices, and pulse power supplies. They are widely used in modern industries and defense fields such as hybrid vehicles, pulse power systems, electromagnetic guns, and electromagnetic launch platforms. With the development of electronic devices towards miniaturization, integration, and high speed, requirements for high energy storage, miniaturization, light weight, low cost, and high reliability are put forward for capacitor components. However, the current capacitor components have unfavorable factors such as low energy storage density, small discharge current, and short life, which make the energy storage capacitor bulky and limit its application. The key to achieving the transformation of capacitor components to high energy storage is to improve the energy storage density of the material.
[0003] Ceramic dielectrics have the advantages of coordinated and controllable performance, wide operating temperature range, and long cycle life. Ferroelectric ceramic materials have high relative dielectric constants, relatively good thermal stability, and high reliability. Therefore, ferroelectric ceramics represented by barium titanate ceramics are widely used as dielectric materials in environments with large capacity and not much temperature change, mainly as dielectrics for medium and low frequency capacitors. However, in fact, due to factors such as grain boundaries, pores, impurities, surface defects, and chemical corrosion, the material is broken down under a relatively low electric field, especially ceramic samples made by traditional solid phase reaction sintering methods usually contain defects such as pores and microcracks, resulting in a low breakdown field strength. Therefore, improving the breakdown field strength has always been the research focus of this type of material in the field of energy storage.
[0004] Silver niobate (AgNbO3) ceramic materials have antiferroelectric-like double hysteresis loops and high polarization strength, and have high dielectric constants, but also have large field-induced deformations, which produce large strains under high electric fields, leading to stress damage. Dielectric materials in the paraelectric phase at room temperature have high dielectric constants, but low breakdown strength. Low dielectric constant ZrSiO4 ceramics have high breakdown field strength, but low dielectric coefficients. Therefore, it is urgent to develop new sintering technologies, reduce sintering temperatures, and prepare high-density energy storage composite ceramics. Summary of the invention
[0005] Aiming at the technical problems of low breakdown field strength and low energy storage density of energy storage ceramics, the present invention proposes a high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25O3 / ZrSiO4 composite ceramics and preparation method thereof, the energy storage performance of silver niobate ceramics is improved by combining B-site ion doping with second phase composite method, and the prepared AgNb 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics have high dielectric properties, high breakdown field strength and high energy storage performance.
[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics comprises the following steps:
[0008] (1) Preparation of AgNb by hydrothermal method 0.5 Zr 0.25 Mg 0.25 O3 nano powder;
[0009] (2) AgNb 0.5 Zr 0.25 Mg 0.25 O3 nanopowder and ZrSiO4 nanopowder are mixed and ball-milled, and then pressed into tablets to obtain ceramic sheets;
[0010] (3) Preparation of AgNb by oscillating pressure sintering of ceramic sheets 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
[0011] The hydrothermal method for preparing AgNb 0.5 Zr 0.25 Mg 0.25 The steps of preparing O3 nanopowder are as follows: calculate and weigh raw powders ⅠAgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 according to the stoichiometric ratio, disperse and dissolve them in solvent Ⅰ together with alkaline reagent Ⅰ and dispersant Ⅰ, and then carry out hydrothermal reaction Ⅰ.
[0012] The mass ratio of the raw material powder I, dispersant I, alkaline reagent I and solvent I is 1:(1-1.3):(1-1.5):(2.6-2.8).
[0013] The temperature of the hydrothermal reaction I is 150-185°C and the time is 8-20h.
[0014] The preparation method of the ZrSiO4 nanopowder is: calculate and weigh the raw material powder II Zr(NO3)3 and tetraethoxysilane according to the stoichiometric ratio, disperse and dissolve them in the solvent II with the alkaline reagent II and the dispersant II, and then perform a hydrothermal reaction II.
[0015] The mass ratio of the raw material powder II, dispersant II, alkaline reagent II and solvent II is 1:(1-1.5):(1-1.6):(1.7-2.9; the temperature of the hydrothermal reaction II is 175-200°C, and the time is 400-650min.
[0016] The dispersant I and dispersant II are both polyvinyl alcohol; the alkaline reagent I and alkaline reagent II are both sodium citrate; the solvent I is water; and the solvent II is ethanol.
[0017] In the step (2), AgNb 0.5 Zr 0.25 Mg 0.25 O3 accounts for AgNb 0.5 Zr 0.25 Mg 0.25 90-98% of the sum of the mass of O3 and ZrSiO4.
[0018] The oscillation pressure sintering method is as follows: placing the ceramic sheet in an oscillation pressure sintering furnace, when the temperature in the furnace is lower than 450°C, the pressure in the furnace is increased to 25-28MPa, and the temperature is kept for 200-400min; then the temperature is increased to 850-940°C, and an oscillation pressure of 30-35MPa is applied on the basis of the pressure of 25-28MPa, the oscillation frequency is 2-4Hz, and the temperature is kept for 30-50min; then under the same oscillation pressure, the temperature is increased to 1050-1150°C, and the temperature is kept for 90-600min, and high energy storage density AgNb is obtained after cooling. 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
[0019] Beneficial effects of the invention: The invention utilizes the idea of ion doping combined with material composite, on the one hand, improves the dielectric properties of AgNbO3 ferroelectric ceramic materials by Zr and Mg ion doping, on the other hand, introduces low dielectric constant ZrSiO4 ceramics to improve the electric field distribution in the composite ceramics, and utilizes the oscillating pressure sintering process to obtain a highly dense, nano-sized microstructure, which synergistically improves the AgNb 0.5 Zr 0.25 Mg 0.25 The prepared composite ceramic has high breakdown field strength, high dielectric properties, energy storage density and good discharge efficiency. The breakdown field strength is 750kV / cm and the maximum energy storage density is 7.73J / cm 3, and has good temperature stability. 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics have the advantages of low cost, nano-scale particles, and excellent energy storage performance. They are suitable for large-scale production and show good application prospects in pulse power energy storage capacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is the SEM image of composite ceramic oxygen.
[0022] Figure 2 This is the breakdown field strength curve of the composite ceramic.
[0023] Figure 3 This is the dielectric constant diagram of the composite ceramic at 1kHz under room temperature conditions.
[0024] Figure 4 This is the energy storage density diagram of the composite ceramic. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramic comprises the following steps:
[0028] (1) Preparation of AgNb by microwave hydrothermal method 0.5 Zr 0.25 Mg 0.25The process of preparing O3 nanopowder is as follows: according to the stoichiometric ratio, raw materials such as AgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 are calculated and weighed, and then the raw materials, polyvinyl alcohol, sodium citrate and water are mixed in a mass ratio of 1:1:1:2.6, and ultrasonicated at 40°C and 40Hz for 70min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 3°C / min, and the reaction is maintained at 185°C for 600min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to preliminarily obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 powder product.
[0029] The process of preparing ZrSiO4 nanopowder by microwave hydrothermal method is as follows: calculate and weigh Zr(NO3)3, tetraethoxysilane and other raw materials according to the stoichiometric ratio, wherein the raw materials, polyvinyl alcohol, sodium citrate and alcohol are mixed in a mass ratio of 1:1:1:1.7. Ultrasonication is carried out at 60°C and 60Hz for 50 minutes, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 3°C / min, and the reaction is maintained at 175°C for 650 minutes. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to obtain a preliminary ZrSiO4 nanopowder product.
[0030] (2) Use a ball mill to mix the above nanopowders, AgNb 0.5 Zr 0.25 Mg 0.25 The mass percentage of O3 is 90%, and the mass percentage of ZrSiO4 is 10%. Anhydrous ethanol and ZrO2 are used as ball milling media during ball milling, the rotation speed is 250r / min, the running direction is adjusted every half an hour, the ball milling time is 12h, and the traditional ceramic tableting process is used for tableting.
[0031] (3) Preparation of AgNb by oscillating pressure sintering 0.5 Zr 0.25 Mg 0.25O3 / ZrSiO4 composite ceramics, the ceramic sheets formed by the traditional ceramic tableting process are placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 450°C, the pressure in the furnace is uniformly increased to 25MPa, the heating rate in the furnace is 3°C / min, and the temperature is kept for 400min; then when the temperature is increased to 850°C, the heating rate in the furnace is 3°C / min, and an oscillating pressure of 30MPa is applied on the basis of the pressure of 25MPa, the oscillation frequency is 2Hz, and the temperature is kept for 30min; then under the same oscillating pressure, the heating rate is continued to be 4°C / min to the target temperature of 1050°C, and the temperature is kept for 600min after reaching the target temperature; the oscillating pressure is unloaded, the constant pressure of 25MPa is maintained, and the cooling is carried out at a cooling rate of 4°C / min. When the temperature in the furnace is cooled to 450°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
[0032] Example 2
[0033] A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramic comprises the following steps:
[0034] (1) Preparation of AgNb by microwave hydrothermal method 0.5 Zr 0.25 Mg 0.25 The process of preparing O3 nanopowder is as follows: according to the stoichiometric ratio, raw materials such as AgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 are calculated and weighed, and then the raw materials, polyvinyl alcohol, sodium citrate and water are mixed in a mass ratio of 1:1.3:1.5:2.8, and ultrasonicated at 40°C and 80Hz for 70min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 5°C / min, and the reaction is maintained at 200°C for 600min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to preliminarily obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 powder product.
[0035] The process of preparing ZrSiO4 nanopowder by microwave hydrothermal method is as follows: calculate and weigh Zr(NO3)3, tetraethoxysilane and other raw materials according to the stoichiometric ratio, wherein the raw materials, polyvinyl alcohol, sodium citrate and alcohol are mixed in a mass ratio of 1:1.5:1.6:2.9. Ultrasonication is performed at 60°C and 90Hz for 50 minutes, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 5°C / min, and the reaction is maintained at 200°C for 400 minutes. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to initially obtain the ZrSiO4 nanopowder product.
[0036] (2) Use a ball mill to mix the above nanopowders, AgNb 0.5 Zr 0.25 Mg 0.25 The mass percentage of O3 is 92%, and the mass percentage of ZrSiO4 is 8%. Anhydrous ethanol and ZrO2 are used as ball milling media during ball milling, the rotation speed is 450r / min, the running direction is adjusted every half an hour, the ball milling time is 12h, and the traditional ceramic tableting process is used for tableting.
[0037] (3) Preparation of AgNb by oscillating pressure sintering 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics, the ceramic sheets formed by the traditional ceramic tableting process are placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 450°C, the pressure in the furnace is uniformly increased to 28MPa, the heating rate in the furnace is 5°C / min, and the temperature is kept for 200min; then when the temperature is increased to 940°C, the heating rate in the furnace is 6°C / min, and an oscillating pressure of 35MPa is applied on the basis of the pressure of 28MPa, the oscillation frequency is 4Hz, and the temperature is kept for 50min; then under the same oscillating pressure, the heating rate is continued to be 6°C / min to the target temperature of 1150°C, and the temperature is kept for 600min after reaching the target temperature; the oscillating pressure is unloaded, the constant pressure of 28MPa is maintained, and the cooling is carried out at a cooling rate of 6°C / min. When the temperature in the furnace is cooled to 500°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
[0038] Example 3
[0039] A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramic comprises the following steps:
[0040] (1) Preparation of AgNb by microwave hydrothermal method 0.5 Zr 0.25 Mg 0.25 The process of preparing O3 nanopowder is as follows: according to the stoichiometric ratio, the raw materials such as AgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 are calculated and weighed, and then the raw materials, polyvinyl alcohol, sodium citrate and water are mixed in a mass ratio of 1:1.2:1.3:2.7, and ultrasonicated at 40°C and 60Hz for 50min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 4°C / min, and the reaction is maintained at 190°C for 450min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to preliminarily obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 powder product.
[0041] The process of preparing ZrSiO4 nanopowder by microwave hydrothermal method is as follows: calculate and weigh Zr(NO3)3, tetraethoxysilane and other raw materials according to the stoichiometric ratio, wherein the raw materials, polyvinyl alcohol, sodium citrate and alcohol are mixed in a mass ratio of 1:1.3:1.4:2.1. Ultrasonication is carried out at 60°C and 80Hz for 40min, and then the mixture is transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 4°C / min, and the reaction is maintained at 185°C for 500min. After the reaction is completed, the mixture is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to obtain a preliminary ZrSiO4 nanopowder product.
[0042] (2) Use a ball mill to mix the above nanopowders, AgNb 0.5 Zr 0.25 Mg 0.25 The mass percentage of O3 is 94%, and the mass percentage of ZrSiO4 is 6%. Anhydrous ethanol and ZrO2 are used as ball milling media during ball milling, the rotation speed is 300r / min, the running direction is adjusted every half an hour, the ball milling time is 11h, and the traditional ceramic tableting process is used for tableting.
[0043] (3) Preparation of AgNb by oscillating pressure sintering 0.5 Zr 0.25 Mg 0.25O3 / ZrSiO4 composite ceramics, the ceramic sheets formed by the traditional ceramic tableting process are placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 24MPa, the heating rate in the furnace is 2°C / min, and the temperature is kept for 200min; then when the temperature is increased to 920°C, the heating rate in the furnace is 4°C / min, and an oscillating pressure of 26MPa is applied on the basis of the pressure of 24MPa, the oscillation frequency is 2Hz, and the temperature is kept for 25min; then, under the same oscillating pressure, the heating rate is continued to be 4°C / min to the target temperature of 1050°C, and the temperature is kept for 300min after reaching the target temperature; the oscillating pressure is unloaded, the constant pressure of 24MPa is maintained, and the cooling is carried out at a cooling rate of 4°C / min. When the temperature in the furnace is cooled to 540°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
[0044] Example 4
[0045] A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramic comprises the following steps:
[0046] (1) Preparation of AgNb by microwave hydrothermal method 0.5 Zr 0.25 Mg 0.25 The process of preparing O3 nanopowder is as follows: according to the stoichiometric ratio, the raw materials such as AgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 are calculated and weighed, and then the raw materials, polyvinyl alcohol, sodium citrate and water are mixed in a mass ratio of 1:1.2:1.4:2.65, and ultrasonicated at 40°C and 70Hz for 50min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 4°C / min, and the reaction is maintained at 195°C for 550min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to preliminarily obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 powder product.
[0047] The process of preparing ZrSiO4 nanopowder by microwave hydrothermal method is as follows: calculate and weigh Zr(NO3)3, tetraethoxysilane and other raw materials according to the stoichiometric ratio, wherein the raw materials, polyvinyl alcohol, sodium citrate and alcohol are mixed in a mass ratio of 1:1.35:1.45:2.7. Ultrasonication is carried out at 60°C and 85Hz for 45min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 4°C / min, and the reaction is maintained at 185°C for 620min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to obtain a preliminary ZrSiO4 nanopowder product.
[0048] (2) Use a ball mill to mix the above nanopowders, AgNb 0.5 Zr 0.25 Mg 0.25 The mass percentage of O3 is 96%, and the mass percentage of ZrSiO4 is 4%. Anhydrous ethanol and ZrO2 are used as ball milling media during ball milling, the rotation speed is 350r / min, the running direction is adjusted every half an hour, the ball milling time is 11h, and the traditional ceramic tableting process is used for tableting.
[0049] (3) Preparation of AgNb by oscillating pressure sintering 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics, the ceramic sheets formed by the traditional ceramic tableting process are placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 22MPa, the heating rate in the furnace is 2°C / min, and the temperature is kept for 150min; then when the temperature is increased to 910°C, the heating rate in the furnace is 3°C / min, and an oscillating pressure of 29MPa is applied on the basis of the pressure of 22MPa, the oscillation frequency is 2Hz, and the temperature is kept for 25min; then under the same oscillating pressure, the heating rate is continued to be 4°C / min to the target temperature of 1030°C, and the temperature is kept for 650min after reaching the target temperature; the oscillating pressure is unloaded, the constant pressure of 22MPa is maintained, and the cooling is carried out at a cooling rate of 4°C / min. When the temperature in the furnace is cooled to 500°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
[0050] Example 5
[0051] A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramic comprises the following steps:
[0052] (1) Preparation of AgNb by microwave hydrothermal method 0.5 Zr 0.25 Mg 0.25 The process of preparing O3 nanopowder is as follows: according to the stoichiometric ratio, the raw materials such as AgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 are calculated and weighed, and then the raw materials, polyvinyl alcohol, sodium citrate and water are mixed in a mass ratio of 1:1.2:1.4:2.65, and ultrasonicated at 40°C and 70Hz for 50min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 4°C / min, and the reaction is maintained at 195°C for 550min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to preliminarily obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 powder product.
[0053] The process of preparing ZrSiO4 nanopowder by microwave hydrothermal method is as follows: calculate and weigh Zr(NO3)3, tetraethoxysilane and other raw materials according to the stoichiometric ratio, wherein the raw materials, polyvinyl alcohol, sodium citrate and alcohol are mixed in a mass ratio of 1:1.35:1.45:2.7. Ultrasonication is carried out at 60°C and 85Hz for 45min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 4°C / min, and the reaction is maintained at 185°C for 620min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to obtain a preliminary ZrSiO4 nanopowder product.
[0054] (2) Use a ball mill to mix the above nanopowders, AgNb 0.5 Zr 0.25 Mg 0.25 The mass percentage of O3 is 98%, and the mass percentage of ZrSiO4 is 2%. Anhydrous ethanol and ZrO2 are used as ball milling media during ball milling, the rotation speed is 350r / min, the running direction is adjusted every half an hour, the ball milling time is 11h, and the traditional ceramic tableting process is used for tableting.
[0055] (3) Preparation of AgNb by oscillating pressure sintering 0.5 Zr 0.25 Mg 0.25O3 / ZrSiO4 composite ceramics, the ceramic sheets formed by the traditional ceramic tableting process are placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 22MPa, the heating rate in the furnace is 2°C / min, and the temperature is kept for 150min; then when the temperature is increased to 910°C, the heating rate in the furnace is 3°C / min, and an oscillating pressure of 29MPa is applied on the basis of the pressure of 22MPa, the oscillation frequency is 2Hz, and the temperature is kept for 25min; then under the same oscillating pressure, the heating rate is continued to be 4°C / min to the target temperature of 1030°C, and the temperature is kept for 650min after reaching the target temperature; the oscillating pressure is unloaded, the constant pressure of 22MPa is maintained, and the cooling is carried out at a cooling rate of 4°C / min. When the temperature in the furnace is cooled to 500°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
[0056] Comparative Examples
[0057] A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 O3 composite ceramic, the preparation method thereof comprises the following steps:
[0058] (1) Preparation of AgNb by microwave hydrothermal method 0.5 Zr 0.25 Mg 0.25 The process of preparing O3 nanopowder is as follows: according to the stoichiometric ratio, the raw materials such as AgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 are calculated and weighed, and then the raw materials, polyvinyl alcohol, sodium citrate and water are mixed in a mass ratio of 1:1.2:1.4:2.65, and ultrasonicated at 40°C and 70Hz for 50min, and then transferred to a hydrothermal reactor and placed in a microwave reactor for reaction. The heating rate of the microwave reactor is 4°C / min, and the reaction is maintained at 195°C for 550min. After the reaction is completed, it is naturally cooled to room temperature, and the sample is taken out, and then the sample is washed with deionized water and alcohol and dried to preliminarily obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 powder product.
[0059] (2) AgNb using ball mill 0.5 Zr 0.25 Mg 0.25O3 nano powder. Anhydrous ethanol and ZrO2 were used as ball milling media during ball milling, the rotation speed was 350r / min, the running direction was adjusted every half an hour, the ball milling time was 11h, and the traditional ceramic tableting process was used for tableting.
[0060] (3) Preparation of AgNb by oscillating pressure sintering 0.5 Zr 0.25 Mg 0.25 O3 ceramics, the ceramic sheets formed by the traditional ceramic tableting process are placed in an oscillating pressure sintering furnace. When the temperature in the furnace is lower than 500°C, the pressure in the furnace is uniformly increased to 22MPa, the heating rate in the furnace is 2°C / min, and the temperature is kept for 150min; then when the temperature is increased to 910°C, the heating rate in the furnace is 3°C / min, and an oscillating pressure of 29MPa is applied on the basis of the pressure of 22MPa, the oscillation frequency is 2Hz, and the temperature is kept for 25min; then, under the same oscillating pressure, the heating rate is continued to be 4°C / min to the target temperature of 1030°C, and the temperature is kept for 650min after reaching the target temperature; the oscillating pressure is unloaded, the constant pressure of 22MPa is maintained, and the cooling is carried out at a cooling rate of 4°C / min. When the temperature in the furnace is cooled to 500°C, the constant pressure is unloaded, and the material is taken out after cooling to room temperature with the furnace to obtain AgNb 0.5 Zr 0.25 Mg 0.25 O3 ceramics.
[0061] Figure 1 For Example 3, AgNb was prepared 0.5 Zr 0.25 Mg 0.25 SEM image of the cross section of O3 / ZrSiO4 composite ceramics shows that the powder size is between 50-150nm and the composite material has dense grains.
[0062] Figure 2 AgNb prepared for Examples 1, 2, 3, 4, and 5 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics and comparative example AgNb 0.5 Zr 0.25 Mg 0.25 The breakdown field strength diagram of O3 ceramics shows that with the increase of ZrSiO4 composite content, AgNb 0.5 Zr 0.25 Mg 0.25 The breakdown field strength of the O3 / ZrSiO4 composite ceramics gradually increases. When the composite amount of ZrSiO4 is 10wt%, the breakdown field strength of the composite ceramics reaches 750kV / cm.
[0063] Figure 3AgNb prepared for Examples 1, 2, 3, 4, and 5 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics and comparative example AgNb 0.5 Zr 0.25 Mg 0.25 Dielectric constant diagram of O3 ceramics. As the composite amount of ZrSiO4 increases, AgNb 0.5 Zr 0.25 Mg 0.25 The dielectric constant of O3 / ZrSiO4 composite ceramics gradually decreases. 0.5 Zr 0.25 Mg 0.25 The dielectric constant of O3 ceramic is 1100, while when the composite amount of ZrSiO4 is 10wt%, the dielectric constant of the composite ceramic is only 500.
[0064] Figure 4 AgNb prepared for Examples 1, 2, 3, 4, and 5 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics and comparative example AgNb 0.5 Zr 0.25 Mg 0.25 The comparison chart of room temperature energy storage density of O3 ceramics shows that when the ZrSiO4 composite content is 8wt%, the energy storage density of the composite ceramic reaches 7.73J / cm 3 .
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high energy storage density AgNb 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The following steps are involved: (1) Preparation of AgNb by hydrothermal method 0.5 Zr 0.25 Mg 0.25 O3 nano powder; (2) AgNb 0.5 Zr 0.25 Mg 0.25 O3 nanopowder and ZrSiO4 nanopowder are mixed and ball-milled, and then pressed into tablets to obtain ceramic sheets; (3) Preparation of AgNb by oscillating pressure sintering of ceramic sheets 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
2. The high energy storage density AgNb according to claim 1 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The hydrothermal method for preparing AgNb 0.5 Zr 0.25 Mg 0.25 The steps of preparing O3 nanopowder are as follows: calculate and weigh raw powders ⅠAgCl, C2H2NbO4, Zr(NO3)3 and Mg(CH3COO)2 according to the stoichiometric ratio, disperse and dissolve them in solvent Ⅰ together with alkaline reagent Ⅰ and dispersant Ⅰ, and then carry out hydrothermal reaction Ⅰ.
3. The high energy storage density AgNb according to claim 2 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The mass ratio of the raw material powder I, dispersant I, alkaline reagent I and solvent I is 1:(1-1.3):(1-1.5):(2.6-2.8).
4. The high energy storage density AgNb according to claim 3 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The temperature of the hydrothermal reaction I is 150-185°C and the time is 8-20h.
5. The high energy storage density AgNb according to any one of claims 1 to 4 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The preparation method of the ZrSiO4 nanopowder is: calculate and weigh the raw material powder II Zr(NO3)3 and tetraethoxysilane according to the stoichiometric ratio, disperse and dissolve them in the solvent II with the alkaline reagent II and the dispersant II, and then perform a hydrothermal reaction II.
6. The high energy storage density AgNb according to claim 5 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The mass ratio of the raw material powder II, dispersant II, alkaline reagent II and solvent II is 1:(1-1.5):(1-1.6):(1.7-2.9; the temperature of the hydrothermal reaction II is 175-200°C, and the time is 400-650min.
7. The high energy storage density AgNb according to claim 6 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The dispersant I and dispersant II are both polyvinyl alcohol; the alkaline reagent I and alkaline reagent II are both sodium citrate; the solvent I is water; and the solvent II is ethanol.
8. The high energy storage density AgNb according to claim 1 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: In the step (2), AgNb 0.5 Zr 0.25 Mg 0.25 O3 accounts for AgNb 0.5 Zr 0.25 Mg 0.25 90-98% of the sum of the mass of O3 and ZrSiO4.
9. The high energy storage density AgNb according to claim 1 0.5 Zr 0.25 Mg 0.25 The preparation method of O3 / ZrSiO4 composite ceramics is characterized in that: The oscillation pressure sintering method is as follows: placing the ceramic sheet in an oscillation pressure sintering furnace, when the temperature in the furnace is lower than 450°C, the pressure in the furnace is increased to 25-28MPa, and the temperature is kept for 200-400min; then the temperature is increased to 850-940°C, and an oscillation pressure of 30-35MPa is applied on the basis of the pressure of 25-28MPa, the oscillation frequency is 2-4Hz, and the temperature is kept for 30-50min; then under the same oscillation pressure, the temperature is increased to 1050-1150°C, and the temperature is kept for 90-600min, and high energy storage density AgNb is obtained after cooling. 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
10. High energy storage density AgNb prepared by the method according to any one of claims 1 to 9 0.5 Zr 0.25 Mg 0.25 O3 / ZrSiO4 composite ceramics.
Citation Information
Patent Citations
Antiferroelectric ceramic and preparation method thereof
CN113024248A
Bi < 3 + > and Y < 3 + > co-doped AgNbO3 anti-ferroelectric energy storage ceramic material as well as preparation method and application thereof
CN118239775A
Dielectric cermic material that contains silver niobium and tantalate
US20040048732A1